2018
DOI: 10.1007/s10878-018-0342-2
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of restoring corrupted colorings

Abstract: In the r-Fix problem, we are given a graph G, a (non-proper) vertex-coloring c : V (G) → [r], and a positive integer k. The goal is to decide whether a proper r-coloring c is obtainable from c by recoloring at most k vertices of G. Recently, Junosza-Szaniawski, Liedloff, and Rzążewski [SOF-SEM 2015] asked whether the problem has a polynomial kernel parameterized by the number of recolorings k. In a full version of the manuscript, the authors together with Garnero and Montealegre, answered the question in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The Coloring Discovery problem has already been studied in the color flipping model and the color swapping model under the names k-Fix [23] and k-Swap [3], respectively. Garnero et al [23] show that, for color flipping, the discovery variant is NP-complete, even for bipartite planar graphs.…”
Section: Coloring Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The Coloring Discovery problem has already been studied in the color flipping model and the color swapping model under the names k-Fix [23] and k-Swap [3], respectively. Garnero et al [23] show that, for color flipping, the discovery variant is NP-complete, even for bipartite planar graphs.…”
Section: Coloring Discoverymentioning
confidence: 99%
“…Garnero et al [23] show that, for color flipping, the discovery variant is NP-complete, even for bipartite planar graphs. Moreover, they show that the problem is W[1]-hard when parameterized by b, even for bipartite graphs, whereas it is fixed-parameter tractable when parameterized by k + b. Interestingly, the latter is not true in the color swapping model, where the problem is W[1]-hard for any fixed k ≥ 3 when parameterized by b [3]. It is also shown that both problems k-Fix and k-Swap are W[1]hard when parameterized by the treewidth of the input graph.…”
Section: Coloring Discoverymentioning
confidence: 99%